Survey of open research data portals and repositories in Argentina - Indart, Camila; Ríos Hilario, Ana Belén; Rodríguez Bravo, Blanca (Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2021)
This article presents the survey to locate the portals and repositories that contain primary research data in Argentina. For this purpose, directories and repositories records, both for data and publications, the repositories included in the Sistema Nacional de Repositorios Digitales, and those harvested by the Sistema de Información Universitaria del Consejo Interuniversitario Nacional in its SIU-BDU 2 service were consulted. Besides, Google search engine and documentary sources on the subject were used. We found 25 repositories containing data and we analyzed some general their characteristics.